Psalm 8: God's glory and humanity's reflected glory - Mare, Leonard P. (Old Testament Essays, 2006)
In this article, the central question that Psalm 8 poses, namely, "what is man?" is investigated. This question is asked and answered in the context of a second question: "Who is God?" The article aims to explore how the relation between God's glory as it is revealed in creation, and the glory of humankind, as the apex of God's creation, should be understood. The article also examines the psalmist's understanding of humankind's God appointed position of rulership over all the works of creation.
free